From policy measures to policy packages - Givoni, M; Macmillen, J; Banister, D; Feitelson, E (Routledge, 2013)
It is increasingly evident that harnessing the potential synergetic relationships that exist between certain policy measures can significantly increase the effectiveness and efficiency of policy interventions. However, while normative sentiments of “integrated policy” and “joined-up government” are well-established, minimal academic attention has, thus far, been paid to considerations of how such relationships might be strategically advanced in promoting effective policy interventions. Framed in relation to transport policy, this paper, thus, tentatively proposes a heuristic framework that seeks to engage with the major conceptual and procedural concerns involved in bona fide “policy packaging”. Wary of naive prescription, the framework is not intended to function as a universal blueprint for policy-making. Rather, we aim to critically examine a number of salient principles that appear to have generic policy relevance across institutional contexts and jurisdictional scales. Fundamentally, the paper argues that while policy packaging can certainly support effective and efficient policy-making—not least through enhancing interventions' implementation and the ex ante mitigation of unintended effects—the packaging process requires a deep and holistic appreciation of policy subsystems, together with a structured approach, if its benefits are to be genuinely realized.